STRATEGY TO IMPROVE EMPLOYEE PERFORMANCE AT PT. PERKEBUNAN NUSANTARA V TAMORA GARDENS, TAPUNG HULU DISTRICT, KAMPAR REGENCY - Agus Pratiwi; Abdul Sadad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
From the production data that has been obtained, the production results at PT. Perkebunan Nusantara V Tamora Gardens continued to show increases, exceeding the stipulated Budget Work Plan (RKAP). Increased production of oil palm, while initially this Tamora Gardens produced rubber. However, the lack of a level of commitment to employees' awareness makes the company constrained. Therefore it is necessary to study strategies to improve employee performance. The purpose of this study was to determine how the strategy for improving employee performance and to determine the factors supporting the strategy for improving employee performance at PT. Perkebunan Nusantara V Tamora Gardens, Tapung Hulu District, Kampar Regency. This type of research is qualitative research with a descriptive approach. From the research results found that the strategy to improve the performance of employees of PT. Perkebunan Nusantara V Tamora Gardens has been going well. Judging from several well-executed indicators, such as motivation by providing direction and meeting economic needs or appropriate remuneration for what employees do, discipline by enforcing existing rules, work environment by providing supportive housing facilities, and commitment by providing sanctions for employees who break the rules. And there are supporting factors in the form of budget and openness. Keywords: Strategy, Improvement, Employee Performance